Telemedicine Acceptance in Malaysia's Healthcare System: Systems Quality and Users Behaviour Matter - Ramli R.; Yahya H. (Institute of Electrical and Electronics Engineers Inc., 2024)
Telemedicine has offered a new way for a remote medical consultation between patients and doctors. While it has been acknowledged that telemedicine has contributed positively towards the quality of global healthcare systems, in some regions users have been reluctant in adapting to remote medical consultancy. Studies have shown telemedicine acceptance has been poor as a result of rejection among the users which has taken its toll on its great potential to healthcare system. This study seeks to establish factors contributing to patients' acceptance towards telemedicine. An acceptance model was developed with a set of hypotheses using the variables identified from the study of literatures. A survey was conducted among Malaysian public who have patronized both private and public medical care to determine their attitudes towards telemedicine and their willingness to embrace this new approach in seeking medical care. The results of the survey have demonstrated that system's quality and users' behaviour play important roles in the acceptance of telemedicine. 2023 IEEE.